2016
DOI: 10.1371/journal.pone.0152378
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecenoic Fatty Acid Isomers in Human Blood Lipids and Their Relevance for the Interpretation of Lipidomic Profiles

Abstract: Monounsaturated fatty acids (MUFA) are emerging health biomarkers, and in particular the ratio between palmitoleic acid (9cis-16:1) and palmitic acid (16:0) affords the delta-9 desaturase index that is increased in obesity. Recently, other positional and geometrical MUFA isomers belonging to the hexadecenoic family (C16 MUFA) were found in circulating lipids, such as sapienic acid (6cis-16:1), palmitelaidic acid (9trans-16:1) and 6trans-16:1. In this work we report: i) the identification of sapienic acid as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 45 publications
5
105
2
1
Order By: Relevance
“…It is important to mention that besides conversion to palmitoleic acid (9cis-16:1) by SCD1, palmitic acid (C16:0) can be converted to another isomer called sapienic acid (6cis-16:1) by fatty acid desaturase 2 (FADS2) enzyme, which is also involved in ω-3 and ω-6 pathway. Sapienic acid detection in human blood and in cancer breast cells demonstrates that it may be synthesized in different tissues and that it plays a significant role in lipid metabolism [43,44]. Considering the results of this study, which showed impaired metabolism of MUFA and ω-3/ω-6 fatty acids in Tff3-/-mice, it is possible that FADS2 enzyme activity is also changed.…”
Section: Cellular Physiologymentioning
confidence: 71%
“…It is important to mention that besides conversion to palmitoleic acid (9cis-16:1) by SCD1, palmitic acid (C16:0) can be converted to another isomer called sapienic acid (6cis-16:1) by fatty acid desaturase 2 (FADS2) enzyme, which is also involved in ω-3 and ω-6 pathway. Sapienic acid detection in human blood and in cancer breast cells demonstrates that it may be synthesized in different tissues and that it plays a significant role in lipid metabolism [43,44]. Considering the results of this study, which showed impaired metabolism of MUFA and ω-3/ω-6 fatty acids in Tff3-/-mice, it is possible that FADS2 enzyme activity is also changed.…”
Section: Cellular Physiologymentioning
confidence: 71%
“…These achievements acquired an important applicative meaning, due to the participation of companies in this Working Group, which were also as coauthor of some papers [90,110,112]. The presence of companies certainly contributed to the discussion of results in terms of scientific innovations that have to be brought to the market for amelioration of the products and improving benefits to consumers.…”
Section: Free Radical Biomimetic and Biological Modelsmentioning
confidence: 92%
“…An important application was the analysis of fatty acid components of red blood cell membrane phospholipids and plasma cholesteryl esters in healthy human subjects and morbidly obese patients, revealing that sapienic acid is an interesting biomarker of metabolism diversion in obese subjects versus controls. These findings are important for deepening biological studies of lipid enzymes, such as delta-9 and delta-6 desaturases as well as LCAT (lecithin cholesterol acyl transferase), that are certainly key steps of metabolism differentiation in health and disease [110].…”
Section: Lipid Isomerizationmentioning
confidence: 98%
“…The example provided by palmitoleic acid (9cis-C16:1), pointed out as significant biomarker in obesity, is indicative since it requires appropriate gas chromatographic conditions to be separated from the positional isomer, i.e., sapienic acid (6cis-C16:1) [6]. This turned out to be very important in the correct examination of fatty acid profiles from the red blood cell membranes and cholesteryl esters of obese and healthy subjects, opening a metabolic alternative for delta-6 desaturase enzymes to process palmitic acid [7]. Nowadays, check-up analyses are made to evaluate presence of essential elements in the body, such as vitamins, minerals, that are more and more revealing the pitfall of the nutrition in industrialized countries, as well as the loss of the nutritional values from the globalized food supply.…”
Section: When Analysis Can Be Usefulmentioning
confidence: 99%
“…It can be used as an indicator of earlier unbalance, highlighting metabolic derangement or insufficient essential fatty acid intakes from the diet, which in each subject can have a specific reason and be targeted with personalized preventive strategies. Over the last decade fatty acid-based functional lipidomics showed its strong contribution to personalized medicine defining several human profiles in pathological conditions, such as obesity [7], autism [8], parenteral nutrition [9], among others, and in various physiological status [1]. The differences reported between healthy controls and groups of subjects with different pathologies created more and more awareness on the value of the associated molecular profiles.…”
Section: When Analysis Can Be Usefulmentioning
confidence: 99%